Toponymy of The Names of Neighborhoods in Teluk Segara District, Bengkulu City, Bengkulu Province - Putri Febriyanti; Kasmantoni; Heny Friantary (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The aim of this research is to discuss the lexical and cultural meaning of naming villages in Teluk Segara District, Bengkulu City, Bengkulu Province, which includes 5 of the 13 existing Villages. This research categorizes them based on naming system aspects, (1) embodiment aspects, (2) social aspects, (3) cultural aspects. This research uses descriptive qualitative research. The data source was obtained from the Traditional Chair of Pondok Besi Subdistrict and the Traditional Chair of Berkas Subdistrict. The data obtained was in the form of interview data in Teluk Segara District. The results of this research reveal that the toponymy of the names of sub-districts in Teluk Segara District, Bengkulu City consists of various categories, including water elements, community social interactions, flora, tangible elements, folklore, nature, settlement patterns, activities, landforms, and building.